Respons Pertumbuhan dan Produksi Kedelai Edamame terhadap Aplikasi POC Daun Kersen (Muntingia calabura L.) - Dian diani Tanjung; Eva Rahmadini; Sukrianto (Fakultas Pertanian - UMJ, 2026)
Edamame is a high-value vegetable soybean commodity with promising export prospects. Sustainable cultivation practices are needed to support its production, including the use of environmentally friendly organic fertilizers. One alternative is liquid organic fertilizer (LOF) derived from cherry leaves, which contain essential nutrients and bioactive compounds beneficial for plant growth. This study evaluated effects of different doses of LOF for growth and yield of edamame. Experiment was conducted from March to May 2025 at Faculty of Agriculture experimental field. A Randomized Complete Block Design with five treatments, five replications was applied. Treatments consisted of an inorganic fertilizer control and cherry leaf LOF at doses of 20, 40, 60, and 80 mL/plant. Observed variables included plant height, branches, flowering, number of pods, and pod weight. Data were subjected to analysis of variance at a 5% significance level. Results indicated that different LOF doses did not significantly affect any observed growth or yield parameters. Nevertheless, LOF doses of 40 mL/plant consistently produced highest values for plant height, branch number, flowering earliness, pod number, and pod weight. These results show cherry leaf LOF may serve as a promising organic fertilizer alternative, although further studies are required to optimize its application and effectiveness.